Slide member and manufacturing method thereof

The sliding member with a Cu-based alloy layer containing Ni and Sn, and an intermediate layer formed by welding, addresses the issue of Cu insertion and cracking in Fe-based substrate sliding members, enhancing strength and reducing wear and adhesion issues.

JP7660547B2Active Publication Date: 2025-04-11DAIDO METAL IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022163240
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-10-11
Publication Date
2025-04-11
Estimated Expiration
2042-10-11

AI Technical Summary

Technical Problem

Existing sliding members with Fe-based substrates and Cu-based alloy layers face issues with Cu insertion into the substrate during welding, leading to cracking and peeling, and require additional steps and complex handling for intermediate layer formation.

Method used

A sliding member with a Fe-based substrate and a Cu-based alloy layer containing 6-12% Ni and 3-9% Sn, where the alloy layer includes a body layer and an intermediate layer formed simultaneously by welding, preventing Cu insertion and reducing cracking and peeling.

Benefits of technology

The solution effectively reduces Cu insertion into the Fe substrate, minimizes cracking and peeling, and improves the strength of the sliding member without increasing man-hours or requiring complex handling, while also reducing wear and enhancing adhesion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007660547000001
    Figure 0007660547000001
  • Figure 0007660547000002
    Figure 0007660547000002
  • Figure 0007660547000003
    Figure 0007660547000003
Patent Text Reader

Abstract

To provide a sliding member and a method for producing the same, which reduce the insertion of a Cu-based alloy into an Fe-based substrate during welding and further improve the strength without requiring an increase in man-hours.SOLUTION: A sliding member 10 includes a substrate 11 containing Fe as a main component and an alloy layer 12 overlaid on the substrate 11 and composed of a Cu-base alloy containing 6 to 12 mass% of Ni and 3 to 9 mass% of Sn. The alloy layer 12 has a body layer 15 and an intermediate layer 16. The body layer 15 is formed of the Cu-base alloy, while the intermediate layer 16 is composed of an alloy containing Fe derived from the substrate 11 in Ni, Sn, and Cu derived from the Cu-base alloy. In any observation section taken along the thickness direction thereof, when the alloy layer 12 is divided at the middle in the thickness direction to set a side close to the substrate 11 as a lower region and the other side as an upper region, a ratio of the total area of hard phases 17 to the observation section of the upper region is 1.2 to 3.0, where the ratio of the total area of the hard phases 17 to the observation section of the lower region is set at 1.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present embodiment relates to a slide member and a manufacturing method thereof. [Background technology]

[0002] Under harsh conditions where a high load is applied and starting and stopping are repeated, high strength and durability are required for the sliding members that support the rotating shaft. In order to ensure strength and durability, an Fe-based base material is used for such sliding members, and a Cu-based alloy layer is laminated on the surface as an alloy layer for bearings.

[0003] In general, Cu-based alloys have a characteristic that the solid solubility limit is low in Fe-based base materials. Therefore, when Fe is dissolved in a Cu-based alloy due to excessive penetration, Fe is easily dissolved, and when a Cu-based alloy layer is formed on an Fe-based base material, there is a problem that cracks and peeling are likely to occur. In particular, when a Cu-based alloy is welded to an Fe-based base material, a phenomenon occurs in which the Cu-based alloy penetrates into the base material, which causes cracks and peeling at the boundary between the base material and the welded layer. Conventionally, in order to reduce the penetration of the Cu-based alloy into the base material, an intermediate layer made of another metal or alloy is formed between the base material and the alloy layer (see Patent Documents 1 and 2, etc.). By forming an intermediate layer, the penetration of the Cu-based alloy into the base material is reduced.

[0004] However, the formation of the intermediate layer requires an additional process in addition to the process of forming a Cu-based alloy on an Fe-based base material. In particular, when the alloy layer is formed by welding from the viewpoint of reducing manufacturing costs, such as in the case of sliding members applied to large equipment, there is a problem that the process of forming the intermediate layer is increased. In addition, since the intermediate layer requires a material different from the base material and the alloy layer, there is a problem that handling is also complicated. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Unexamined Patent Publication No. 179020 / 1983 [Patent Document 2] Japanese Patent Application Publication No. 62-267078 Summary of the Invention [Problem to be solved by the invention]

[0006] Therefore, an object of the present invention is to provide a sliding member and a manufacturing method thereof that reduce the penetration of Cu-based alloy into an Fe-based base material during welding without requiring an increase in labor hours, thereby further improving strength. [Means for solving the problem]

[0007] In order to solve the above problems, a slide member according to one embodiment includes a substrate containing Fe as a main component, and an alloy layer made of a Cu-based alloy containing 6 to 12 mass % of Ni and 3 to 9 mass % of Sn and laminated on the substrate. The alloy layer has a main layer and an intermediate layer. The main layer is formed of the Cu-based alloy. The intermediate layer is made of an alloy containing Ni, Sn, and Cu derived from the Cu-based alloy and Fe derived from the substrate. The alloy layer has a hard phase consisting of a compound of Ni, Sn, and Cu derived from the Cu-based alloy, and a flake phase containing the hard phase and a matrix of the Cu-based alloy. When the alloy layer is divided in the middle of the thickness direction of the alloy layer in an arbitrary observation cross section cut in the thickness direction of the alloy layer, and the substrate side is set as a lower region and the opposite side to the substrate is set as an upper region, if the ratio of the total area of ​​the hard phase in the observation cross section in the lower region is 1, the ratio of the total area of ​​the hard phase in the observation cross section in the upper region is 1.2 to 3.0.

[0008] The alloy layer has a main layer and an intermediate layer. The main layer and the intermediate layer are formed simultaneously when the alloy layer is formed by welding. That is, the Cu-based alloy deposited on the substrate during welding generates an alloy that becomes the intermediate layer from Ni, Sn, and Cu derived from the Cu-based alloy and Fe derived from the substrate at the interface with the Fe of the substrate. On the other hand, in the region other than the interface between the alloy layer and the substrate, the main layer is formed from the Cu-based alloy. Thus, in this embodiment, when the alloy layer is welded, in addition to the main layer, an intermediate layer is simultaneously formed at the interface with the substrate. Ni contained in the Cu-based alloy has a high affinity with Fe forming the substrate. Therefore, Ni contained in the Cu-based alloy and Fe contained in the substrate form an intermediate layer of a different composition from the Cu-based alloy that becomes the alloy layer at the interface between the alloy layer and the substrate. That is, the intermediate layer is formed simultaneously with welding of the alloy layer. As a result, the phenomenon of Cu-based alloy being inserted into the Fe substrate during welding is prevented by the intermediate layer, and cracking and peeling can be reduced.

[0009] In one embodiment, the ratio of the total area of ​​the hard phases in the observation cross section in the lower region of the alloy layer is 1.2 to 3.0 when the ratio of the total area of ​​the hard phases in the observation cross section in the lower region is 1. The hard phase is harder than the matrix of the Cu-based alloy constituting the alloy layer. Therefore, when the alloy layer slides against the counter member, the hard phase contributes to reducing the wear of the alloy layer. On the other hand, the hard phase is a factor in reducing the adhesive force between the substrate and the alloy layer. Therefore, by making the distribution ratio of the hard phase different between the lower region and the upper region, the wear of the alloy layer is reduced in the upper region, and peeling between the substrate and the alloy layer is reduced in the lower region. Therefore, the strength can be further improved without requiring additional steps for forming the intermediate layer. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a schematic cross-sectional view showing a structure of a sliding member according to an embodiment; [Diagram 2] FIG. 2 is a schematic diagram showing the structure of a hard phase and a flake phase in an alloy layer of a slide member according to one embodiment; [Diagram 3] FIG. 1 is a schematic diagram illustrating a structure of a sliding member according to an embodiment; [Figure 4] Schematic diagram showing a sliding member according to an embodiment applied to a rotating shaft portion. [Diagram 5] FIG. 1 is a schematic diagram showing a welding apparatus for welding an alloy layer of a slide member to a base material according to an embodiment; [Figure 6] FIG. 1 is a schematic diagram showing a test piece for a sliding member according to an embodiment; [Figure 7] Schematic diagram of Figure 6 as seen from the direction of arrow VII [Figure 8] FIG. 1 is a schematic diagram showing a test device for performing a seizure test and a wear test on a sliding member according to an embodiment; [Figure 9] Schematic diagram of the test piece mounted on the test device as seen from the direction of arrow IX in Figure 8. [Figure 10] Schematic diagram showing the test conditions for the seizure test [Figure 11] Schematic diagram showing the test conditions for the wear test [Figure 12] Schematic diagram showing test results of examples and comparative examples DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, a sliding member according to an embodiment will be described with reference to the drawings. As shown in Fig. 1, slide member 10 includes a substrate 11 and an alloy layer 12. Alloy layer 12 is provided on substrate 11 by welding to interface 13, which is one surface side of substrate 11. In slide member 10, the surface of alloy layer 12, i.e., the end face of alloy layer 12 opposite substrate 11, becomes slide surface 14 that slides against a counter member (not shown).

[0012] The substrate 11 is a so-called back metal layer, and is made of a material mainly composed of Fe. As the substrate 11 mainly composed of Fe, for example, hypo-eutectoid steel, eutectoid steel, hyper-eutectoid steel, cast iron, high speed steel, tool steel, austenitic stainless steel, ferritic stainless steel, etc. can be used.

[0013] The alloy layer 12 is a Cu-based alloy containing Cu as a main component. The alloy layer 12 is a CuSnNi alloy containing 6 to 12 mass% Ni and 3 to 9 mass% Sn. That is, the alloy layer 12 contains at least Ni and Sn. This alloy layer 12 has a main body layer 15 and an intermediate layer 16. The main body layer 15 is formed of a Cu-based alloy that forms the alloy layer 12. That is, the main body layer 15 is a Cu-based alloy containing Ni, Sn, and unavoidable impurities. The intermediate layer 16 is an alloy containing Ni, Sn, and Cu derived from the Cu-based alloy that forms the alloy layer 12, and Fe derived from the substrate 11. That is, the intermediate layer 16 is formed of an alloy of Ni, Sn, Cu, and unavoidable impurities derived from the Cu-based alloy, and Fe derived from the substrate 11. Ni contained in the Cu-based alloy has a high affinity with Fe that constitutes the substrate 11. Therefore, when alloy layer 12 is formed on substrate 11 by welding, Ni contained in molten alloy layer 12 migrates to interface 13 with substrate 11, which contains Fe as a main component. As a result, intermediate layer 16 containing Fe is formed at interface 13 between substrate 11 and alloy layer 12. As a result, alloy layer 12 has main body layer 15 made of a Cu-based alloy and intermediate layer 16 made of an alloy containing Fe.

[0014] The alloy layer 12 has a hard phase 17 and a flake phase 18 as shown in FIG. 2. The hard phase 17 is a metastable phase made of an alloy such as (Cu·Ni)3Sn derived from Ni, Sn, and Cu contained in the Cu-based alloy. In the alloy layer 12, the hard phase 17 and the flake phase 18 are surrounded by a matrix 19 of a Cu-based alloy. Of these, the flake phase 18 is a structure in which a portion made of a component forming the hard phase 17 and a portion made of a component forming the matrix 19 are layered and overlapped. The flake phase 18 exists so as to surround the whole or a part of the hard phase 17 by this structure. The alloy layer 12 is composed of the layered flake phase 18 that surrounds the hard phase 17 and the matrix 19.

[0015] The alloy layer 12 is specified for the ratio R of the total area of ​​the hard phase 17 in any cross section cut in the thickness direction. Specifically, as shown in FIG. 3, the alloy layer 12 in which the observation cross section S is set is set with the middle H of the thickness of the alloy layer 12 as the boundary, the substrate 11 side as the lower region A1, and the opposite side to the substrate 11, i.e., the sliding surface 14 side as the upper region A2. In this case, if the ratio of the total area of ​​the hard phase 17 in the observation cross section S in the lower region A1 is 1, the ratio R of the total area of ​​the hard phase 17 in the observation cross section S in the upper region A2 is 1.2 to 3.0. In other words, the hard phase 17 contained in the upper region A2 is 1.2 to 3.0 times more than that in the lower region A1.

[0016] The hard phase 17 is harder than the matrix of the Cu-based alloy constituting the alloy layer 12. Therefore, when the alloy layer 12 slides against a counter member (not shown), the hard phase 17 contributes to reducing the wear of the alloy layer 12. On the other hand, the hard phase 17 affects the adhesive force between the substrate 11 and the alloy layer 12. When a load from a counter member (not shown) is applied to the sliding member 10 including the alloy layer 12, the sliding member 10 is deformed, for example, deflected. This deformation is a cause of peeling between the substrate 11 and the alloy layer 12. If a large amount of the hard phase 17 is present in a position close to the interface 13, peeling between the substrate 11 and the alloy layer 12 is likely to occur. Therefore, by making the distribution of the hard phase 17 different between the lower region A1 and the upper region A2, the wear of the alloy layer 12 is reduced in the upper region A2, while the peeling between the substrate 11 and the alloy layer 12 is reduced in the lower region A1. As a result, the slide member 10 can improve the adhesion between the substrate 11 and the alloy layer 12, and can improve the seizure resistance and wear resistance of the alloy layer 12.

[0017] The sliding member 10 formed in this embodiment can be suitably used for a rotating member 20 having a large scale and high surface pressure, such as a rotating shaft or a bearing of a wind power generator, as shown in FIG. 4. In the example shown in FIG. 4, the rotating member 20 includes a substrate 11 and an alloy layer 12. The alloy layer 12 is directly provided on the rotating shaft portion 21, which is the substrate 11, by welding. In this case, the outer peripheral surface of the alloy layer 12 forms the sliding surface 14. By providing the alloy layer 12 directly on the rotating shaft portion 21 by welding in this manner, the rotating member 20 can also handle high surface pressure. In addition, when the sliding member 10 is used for the rotating member 20 of a wind power generator in this manner, the alloy layer 12 is built up on the rotating shaft portion 21, which is the substrate 11, by welding, and then cut to a thickness of about 0.5 mm. At this time, the thickness of the intermediate layer 16 formed in the alloy layer 12 at the interface 13 with the substrate 11 is about 1.0 to 20 μm. The roughness Ra of the sliding surface 14 is set to about 0.3 to 0.6. The sliding member 10 may be configured, for example like a bearing member, in which the alloy layer 12 is formed by welding on the inner peripheral side of a cylindrical, semi-cylinder, or tubular piece-shaped substrate 11 divided into three or more pieces in the circumferential direction.

[0018] Next, a method for manufacturing the slide member 10 will be described. The alloy layer 12 is formed by welding on the surface of the base material 11, which is mainly composed of Fe. Specifically, the alloy layer 12 is formed by welding the welding material 31 to the base material 11 as shown in FIG. 5, and using the welding material 31 as a main material. The welding material 31 is a Cu-based alloy that forms the alloy layer 12, and contains Ni as an additive element that has a high affinity with the base material 11. In addition to Ni, the welding material 31 contains Sn and unavoidable impurities. That is, the welding material 31 is a Cu-based alloy that contains Ni, Sn, and unavoidable impurities. The additive element is not limited to Ni, and any additive element that has a high affinity with Fe, which is the base material 11, can be used.

[0019] The welding material 31 is formed into a string-like shape by twisting together, for example, wire or a plurality of fibrous metals, and is supplied to a supply section 33 of a welding device 32 as shown in FIG. 5. The supplied welding material 31 is melted by arc discharge between the material 31 and the base material 11, and transferred to the base material 11. The welding method used in the welding device 32 is preferably MIG welding using an inert gas as the shielding gas 34. More preferably, the welding method is MIG welding using a CMT method in which the supplied welding material 31 is driven forward or backward at high speed. Furthermore, the welding method may be TIG welding if certain conditions are met. During this welding, the heat-affected depth in the base material 11 is preferably 200 μm or less.

[0020] By welding the welding material 31 to the base material 11, a weld layer 35 is formed on the base material 11. At the same time, the molten welding material 31 generates an alloy with Fe, which is a base material element forming the base material 11, at the interface 13 with the base material 11. That is, the molten high-temperature welding material 31 transfers to the base material 11 and generates an alloy containing Fe, which is a base material element, at the interface 13 with the base material 11. The alloy generated at the interface 13 with the base material 11 becomes the intermediate layer 16 shown in FIG. 1.

[0021] By welding the welding material 31 to the base material 11, the high-temperature welding material 31 melts the surface of the base material 11 at the interface 13 with the base material 11 and is mixed with Fe, which is an element of the base material. As a result, the welded layer 35 formed by the welding material 31 has an intermediate layer 16 made of an alloy containing Fe at the interface 13 with the base material 11, and has a main body layer 15 not containing Fe on the side farther from the base material 11 than the intermediate layer 16. In other words, the welded layer 35 has an intermediate layer 16 containing Fe therein, and a main body layer 15 not containing Fe.

[0022] This welded layer 35 is a precursor of the alloy layer 12 in the slide member 10 shown in FIG. 1. When the welded layer 35 is formed on the substrate 11 by welding, the welded layer 35 is subjected to a heat treatment. Specifically, the welded layer 35 formed on the substrate 11 is subjected to an aging treatment at a temperature of 370 to 430°C for 4 to 10 hours. This aging treatment causes the welded layer 35 to produce a hard phase 17 and a flaky phase 18. That is, by the aging treatment, the welded layer 35 produces a structure in which the hard phase 17 and the flaky phase 18 are formed in layers as shown in FIG. 2, and becomes the alloy layer 12.

[0023] After the aging treatment, the slide member 10 having the alloy layer 12 formed thereon is cut to a desired thickness. The alloy layer 12 is cut to a thickness of, for example, 0.5 mm or less. The average diameter of the hard phase 17 becomes 0.5 to 2.0 μm by the aging treatment. The surface roughness Ra of the cut alloy layer 12 is preferably 0.3 to 0.6.

[0024] As described above, the alloy layer 12 according to one embodiment has the main layer 15 and the intermediate layer 16. The main layer 15 and the intermediate layer 16 are formed simultaneously when the alloy layer 12 is formed by welding. That is, the Cu-based alloy deposited on the substrate 11 during welding generates an alloy that becomes the intermediate layer 16 from Ni, Sn, and Cu derived from the Cu-based alloy and Fe derived from the substrate 11 at the interface 13 with the substrate 11. On the other hand, in the region other than the interface 13, the main layer 15 is formed from the Cu-based alloy. Thus, in this embodiment, when the alloy layer 12 is welded, in addition to the main layer 15, the intermediate layer 16 is simultaneously formed at the interface 13 with the substrate 11. As a result, the phenomenon in which Cu contained in the alloy layer 12 is inserted into the Fe of the substrate 11 is prevented by the intermediate layer 16, and cracks and peeling caused by this insertion are reduced.

[0025] In one embodiment, when the ratio of the total area of ​​the hard phase 17 in the observation cross section S in the lower region A1 is 1, the ratio R of the total area of ​​the hard phase 17 in the observation cross section S in the upper region A2 is 1.2 to 3.0. By making the distribution ratio of the hard phase 17 different between the lower region A1 and the upper region A2, wear of the alloy layer 12 in the upper region A2 is reduced, and peeling between the substrate 11 and the alloy layer 12 in the lower region A1 is reduced. Therefore, the strength of the slide member 10 can be further improved without requiring additional steps for forming the intermediate layer 16.

[0026] Examples and comparative examples of the sliding member 10 will be described below. The examples and comparative examples were evaluated by adhesion tests and sliding tests. The test pieces were overlay-welded to an Fe-based substrate 11 with a Cu9Ni6Sn alloy as the alloy layer 12. The Cu9Ni6Sn alloy was welded by MIG welding while repeatedly feeding the alloy wire into the molten pool at high speed in forward and reverse directions. After the alloy layer 12 was formed by welding, it was subjected to the heat treatment specified in the examples and comparative examples. After the heat treatment, the test pieces were machined, such as by cutting and polishing, to form a predetermined shape.

[0027] In the adhesion test, the strength of the slide member 10 was evaluated in terms of the adhesive strength between the substrate 11 and the alloy layer 12. In the adhesion test, a test piece 40 was used in which the substrate 11 and the alloy layer 12 were joined with the same joining area, as shown in Figs. 6 and 7. The adhesive strength was measured by applying a tensile load to both ends of the test piece 40 and measuring the maximum tensile force at which the joint 41 broke. The test piece 40 used had an overlap of 9 mm x 0.3 mm at the joint 41 between the substrate 11 and the alloy layer 12, and a joining area of ​​2.7 mm. 2 It is.

[0028] In the sliding test, the strength of the sliding member 10 was evaluated by a seizure test and a wear test. In the seizure test, the maximum surface pressure at which the sliding member 10 did not seize was evaluated as the seizure resistance. In the wear test, the wear amount of the sliding member 10 was evaluated as the wear resistance. In the seizure test and wear test in the sliding test, a test piece 50 formed in an arc-shaped ring shape was attached to a holder 51 as shown in Figs. 8 and 9, and the test piece 50 attached to the holder 51 was pressed against a cylindrical test shaft 52 for measurement. In the sliding test, the examples and comparative examples of the sliding member 10 were evaluated by a seizure test under the conditions shown in Fig. 10 and a wear test under the conditions shown in Fig. 11.

[0029] The evaluation results of the examples and comparative examples are shown in FIG. 12. In the adhesion test, the adhesive strength was 300 N / mm 2 Above this level was deemed "qualified." In the seizure test, a maximum surface pressure of 18 MPa or more that did not cause seizure was deemed "qualified." In the abrasion test, a wear amount of 5 μm or less was deemed "qualified." Note that in the seizure test, the maximum value was 25 MPa due to the constraints of the performance of the testing equipment.

[0030] Although Examples 1 to 7 have different materials for the base material 11 or different welding methods, the Cu-based alloy forming the alloy layer 12 is common. That is, Examples 1 to 7 have common compositions for the main layer 15 and intermediate layer 16 included in the alloy layer 12. In Examples 1 to 7, the heat treatment temperature is 370 to 430°C and the time is 4 to 10 hours. As a result of this heat treatment, when the ratio of the total area of ​​the hard phase 17 in the observation cross section S in the lower region A1 is set to 1, the ratio R of the total area of ​​the hard phase 17 in the observation cross section S in the upper region A2 is 1.2 to 3.0 in Examples 1 to 7. These Examples 1 to 7 have an adhesive strength of 300 N / mm 2 Moreover, in Examples 1 to 7, the maximum surface pressure at which seizure does not occur is 25 MPa or more, and the amount of wear is 5 μm or less.

[0031] Comparative Example 1In Comparative Example 1, the heat treatment temperature is low at 360°C. Therefore, in Comparative Example 1, the average grain size of the hard phase 17 generated is small compared to Examples 1 to 7, and the ratio R of the total area of ​​the hard phase 17 is also small. As a result, it is understood that the result of the sliding test is deteriorated in Comparative Example 1. On the other hand, in Comparative Example 2, the heat treatment temperature is high at 450°C. Therefore, in Comparative Example 2, the average grain size of the hard phase 17 is large compared to Examples 1 to 7. Also, in Comparative Example 2, the ratio R of the total area of ​​the hard phase 17 in the upper region A2 to the lower region A1 is excessively large. As a result, it is understood that the result of the sliding test is deteriorated in Comparative Example 2.

[0032] None of Comparative Examples 3 to 5 contains an additive element having a high affinity with Fe in the alloy layer 12. Therefore, in Comparative Examples 3 to 5, a layer corresponding to the intermediate layer 16 is not formed in the alloy layer 12, and the hard phase 17 is not generated even when heat treatment is applied. As a result, it is found that Comparative Examples 3 to 5 show poor results in both the adhesion test and the sliding test. In particular, in Comparative Example 5, the substrate 11 and the Cu-based alloy layer 12 are not bonded to each other, and the adhesion test is not successful.

[0033] In Comparative Example 6, the composition of the alloy layer 12 and the heat treatment conditions are the same as those in Example 1, but the alloy layer 12 does not have a layer corresponding to the intermediate layer 16. Therefore, in Comparative Example 6, the hard phase 17 is distributed almost uniformly throughout the alloy layer 12, and the ratio R of the total area is 1.0. As a result, in Comparative Example 6, the result of the sliding test is acceptable, but the adhesive strength is insufficient. In Comparative Examples 7 and 8, a layer corresponding to the intermediate layer 16 having high affinity with the substrate 11 is formed on the substrate 11 before the formation of the alloy layer 12. In Comparative Examples 7 and 8, the adhesive strength between the substrate 11 and the alloy layer 12 is high, but the composition of the alloy layer 12 is different, so that the hard phase 17 is not generated even when heat treatment is applied. As a result, the results of the sliding test are poor in Comparative Examples 7 and 8.

[0034] The present invention described above is not limited to the above-described embodiment, and can be applied to various embodiments without departing from the gist of the invention. [Explanation of symbols]

[0035] In the drawing, 10 denotes a sliding member, 11 denotes a substrate, 12 denotes an alloy layer, 13 denotes an interface, 15 denotes a main layer, 16 denotes an intermediate layer, 17 denotes a hard phase, 18 denotes a flake phase, and 19 denotes a matrix.

Claims

1. A base material containing Fe as a main component and selected from hypo-eutectoid steel, eutectoid steel, hyper-eutectoid steel, cast iron, high-speed steel, tool steel, austenitic stainless steel, and ferritic stainless steel; an alloy layer formed on the substrate, the alloy layer being made of a Cu-based alloy containing 6 to 12 mass % Ni, 3 to 9 mass % Sn, and the balance being Cu and unavoidable impurities; A sliding member comprising: The alloy layer is A main body layer formed of the Cu-based alloy; An intermediate layer made of an alloy containing Ni, Sn, and Cu derived from the Cu-based alloy and Fe derived from the base material, The hard phase is made of a compound of Ni, Sn, and Cu derived from the Cu-based alloy, and the flake phase includes a matrix of the hard phase and the Cu-based alloy; In any observation cross section cut in the thickness direction of the alloy layer, when the alloy layer is divided at the middle of the distance in the thickness direction from the surface of the substrate before the alloy layer is formed to the surface of the alloy layer opposite the substrate after the alloy layer is formed, the substrate side is set as a lower region, and the opposite side to the substrate is set as an upper region, When the ratio of the total area of ​​the hard phase in the observation cross section in the lower region is 1, the ratio of the total area of ​​the hard phase in the observation cross section in the upper region is 1.2 to 3.

0. Sliding member.

2. A method for manufacturing the sliding member according to claim 1, a welding process in which a welding material containing an additive element having high affinity with the base material is welded to the base material to form a weld layer; an intermediate layer forming step of forming an intermediate layer, which includes the additive element contained in the welding material and a base material element forming the base material, at an end of the welded layer on the base material side, simultaneously with the welding step; an aging step of forming the welded layer including the intermediate layer by subjecting the welded layer to a heat treatment to generate the alloy layer; Including, A method for manufacturing a sliding member.

3. The aging process is performed at a temperature of 370 to 430°C for a time of 4 to 10 hours. The method for producing the sliding member according to claim 2.

Citation Information

Patent Citations

  • JP1981-179020A

  • Build-up welding method of aluminum bronze to ferrous base metal

    JP1987267078A

  • Cu-based sintered alloy

    JP1993195117A

  • Material composite in strip form and its use, composite sliding element consisting of the material composite in strip form

    JP2007297706A

  • Cu-Ni-Sn Alloy Overlay for Bearing Surfaces on Oilfield Equipment

    US20150111793A1